Breath Figures decorated silicon oxinitride ceramic surfaces with controlled Si ions release for enhanced osteoinduction. Issue 4 (14th October 2018) - Carlomagno, Cristiano; Motta, Antonella; Sorarù, Giandomenico; Aswath, Pranesh; Migliaresi, Claudio; Maniglio, Devid
Abstract: Bioactive coatings are usually applied to bone and dental prostheses to enhance the integration and their stability in the bone. Recently, silicon (Si) oxynitride ceramics have been demonstrated to possess osteoconductive properties due to the release of Si ions, particularly important in the early stage of bone formation. In addition, the pattern of the bone contacting surface has been reported to affect cells' differentiation and metabolic activity. In this work, we propose the Breath Figure (BF) process combined with a pyrolysis step, starting from a photo‐crosslinkable alkoxy silicone precursor, as a method to realize bioactive patterned coating on metal bone and dental prostheses. Four different surface patterned coatings were applied to Ti4Al6V disks starting from solutions with different precursor concentrations. Morphology, chemical composition, and Si ions' release were evaluated and compared. Moreover, all samples underwent to biological in vitro testing with human mesenchymal stem cells (hMSCs) in comparison with the uncoated titanium alloy. The results indicated that the Si released from the coatings determined an increase in the cellular activity with the BF pattern influencing the hMSCs' initial adhesion and proliferation. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1284–1294, 2019.